A Review Study Of Research Conducted On Vitamin D - Ali, Enas H.; Al-Ghanimi, Hussein H.; Mohammed, Ruqaya K.; Al-dedah, Rusul M.; Alawdi, Barakat W. (Scientific Journal of Medical Research, 2022)
One of the most popular subjects right now in academia, medicine, and general culture is vitamin D. Over the past few decades, Researchers have amassed a mountain of evidence to support their contention that the widespread lack of vitamin D not only has a harmful impact on the human skeletal system but also contributes to the development and progression of a wide range of contemporary diseases, including cancer, diabetes, autoimmune disorders, and cardiovascular illnesses. Eight thorough reviews that make up this Special Issue’s "Vitamin D and Human Health" overview recent developments in our knowledge of vitamin D’s pleiotropic effect. Eight publications offer fresh perspectives on vitamin D research and point to emerging areas. Vitamin D controls the metabolism of calcium and phosphate and preserves a healthy, mineralized skeleton. As an immunomodulatory hormone, it is also known.